(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The research progress of the thesis of the master’s degree in technology education at the Universidad Distrital Francisco José de Caldas in terms of the development of a virtual mathematical game allows us to analyze both the evolution of cognitive schemes proposed by Marshall (1995) and the Hypothetical Learning Trajectories (THA) by Simon (1995) during the solution of the game “Turning the tables” by Stewart (2004). Since solving problems in mathematics is a difficulty for students (Socas, Hernández, & Palarea, 2014), their cognitive process is not clear during their learning as they are aware of this. The collection of data and modeling of situations with technological devices that are analyzed through the sequential method of mixed methods, from graphs obtained in the MATLAB software, which shows the representation of the movements of the players in the problem space and , the results derived from the verbal story technique that characterizes the verbal and body language of each player, serve to identify how the cognitive schemes evolve during the development of the game following a THA, contributing to the renewal in education.